Age-adjusted infarct volume cut-off points improve stroke outcome prognostication beyond modeling with age and infarct volume. (15th March 2021) - Bouslama, Mehdi; Haussen, Diogo C; Rodrigues, Gabriel Martins; Barreira, Clara M; Dehkharghani, Seena; Frankel, Michael R; Nogueira, Raul G
Abstract : Background: Age and infarct volume are among the most powerful predictors of outcome after large vessel occlusion acute strokes (LVOS). Objective: To study the impact of age-adjusted final infarct volume (FIV) on functional outcomes. Methods: Review of a prospectively collected thrombectomy database at a tertiary care center between September 2010 and February 2018. Consecutive patients with anterior circulation LVOS who achieved full reperfusion (modified Thrombolysis in Cerebral Infarction 3) were categorized into four age groups: (G1) <60 years, (G2) 60–69, (G3) 70–79, (G4) ≥80 years. The Youden Index was used to identify the optimal FIV cut-off point for good outcome (modified Rankin Scale score 0–2) discrimination in each group and the overall population. The predictive ability of these specific thresholds was evaluated using binary logistic regressions and compared with the non-age-adjusted cut-off point. Results: 516 patients were analyzed (G1: n=171, G2: n=130, G3: n=103, G4: n=112). Patients with poor outcome had a larger FIV in each group (p<0.01 for all). The target FIV cut-off point decreased with increased age: G1: 45.7 mL (sensitivity 56%, specificity 80%); G2: 30.4 mL (sensitivity 63%, specificity 75%); G3: 20.2 mL (sensitivity 76%, specificity 65%); G4: 16.9 mL (sensitivity 68%, specificity 70%). The non-age-adjusted cut-off point was 19.2 mL (sensitivity 70%, specificity 59%). In multivariate analysis, adjusting for confounders including age and FIV, achieving a FIV less than the age-adjusted threshold was an independent predictor of good outcome (aOR=2.72, 95% CI 1.41 to 5.24, p<0.001). In contrast, a similar model including the non-age-adjusted target cut-off point failed to reveal an association with good outcome (aOR=1.72, 95% CI 0.93 to 3.19, p<0.085). Furthermore, the latter model had a weaker outcome predictive ability as assessed by the Akaike information criterion (409 vs 403). Conclusions: Age-adjusted infarct volume represents a strong outcome discriminator beyond age and infarct volume in isolation and might help to refine patient selection and improve outcome prognostication in stroke thrombectomy.